ECONOMIC POTENTIAL OF SMALL BUSINESS ENTERPRISE: STRUCTURE AND METHODOLOGICAL APPROACHES TO FORMATION (Development Service Industry Management, 2025)
The article examines the economic potential of a small business enterprise, defined as an innovation driver for large corporations, adapting to digital transformation and online commerce. For the analysis, the theoretical definition of economic potential is substantiated, which is determined by the set of qualities of the system of opportunities of a small business enterprise relevant for scientific and technological development and growth. The evolution of the economic potential of an enterprise is considered, but despite the contribution of scientists, there is a lack of research on small business and updated methods for assessing economic potential in the context of technological change. It is determined that in Ukraine small business creates jobs and stimulates innovation but faces problems of financing and competition. To develop the economic potential of enterprises, new technologies, non-standard sources of financing for small businesses, crowdfunding, microcredit, etc. are necessary. Financial sustainability, technological development, and competitive environment are key aspects of economic potential. It is analyzed that financial factors, competitive environment, economic conditions and technological innovations affect the economic potential of a small business enterprise. Stable financing and investments are becoming important, but high rates and limited investment are obstacles. Digital modernization requires financing and personnel. Management skills are the basis for effective management of the economic potential of a small business enterprise. In conclusion, it is proposed to improve the methods of forming the economic potential of an enterprise, which help optimize small business development strategies in conditions where problems with investments and regulatory requirements persist; as well as adapt to macroeconomic challenges and implement an innovative strategy for the sustainable development of the economic potential of a business. A systematic approach and the combination of various methodological approaches are the key to the successful development of the economic potential of a small business enterprise.
Keywords: economic potential; potential; competitive environment; market; enterprise; small business; digitalization; digital technologies